Partners in crime – How cabbage seed weevil assists brassica pod midge in damaging pods of winter oilseed rape in fields in Southern Sweden - Heithausen, Sarah (2020)
The brassica pod midge (Dasineura brassicae) has emerged as an important pest causing problems in Winter Oilseed Rape (WOSR) (Brassica napus ssp. napus) production in Southern Sweden during recent years. Adult female D. brassicae oviposit into WOSR pods. After hatching from the eggs, the D. brassicae larvae feed on the inside of the pod, causing deformation and premature opening of the pod, which can result in dramatic yield losses. As the ovipositor of the adult female D. brassicae is too weak to pierce WOSR pod walls, oviposition is mostly done in pre-damaged WOSR pods. Most of these damages that are utilized for oviposition by D. brassicae are caused by the cabbage seed weevil (Ceutorhynchus obstrictus). The weevil feeds on the WOSR pods, thereby causing damages that facilitate oviposition by D. brassicae. Pest control measures are therefore directed against C. obstrictus as the brassica pod midge is extremely difficult to control. More information about the phenology and the combined effect of the two insect species is needed in order to create pest control as sustainable as possible. In this study, C. obstrictus and D. brassicae were monitored during six weeks from May until June 2019 in 20 different WOSR fields around Scania, the southernmost province of Sweden. Different active (visual count) and passive (yellow pan traps, yellow sticky traps) monitoring methods were used to assess the abundance of C. obstrictus and D. brassicae in the 20 WOSR fields and the effect of their presence on the amount of pod damage by D. brassicae. Trap samples were collected weekly and analyzed in the laboratory. At the end of the study period, pod damage was assessed in each field. The number of captured insects of the two species was very low in comparison with previous studies from the last two years, so was the percentage of pod damage. Phenology of C. obstrictus deviated from the expected pattern: Usually the cabbage seed weevil can be observed in a WOSR field earlier in the season than the pod gall midge. In this study C. obstrictus captures peaked 2-3 weeks later than D. brassicae captures, presumably creating less oviposition possibilities for D. brassicae. Nonetheless, the brassica pod midge could benefit from the presence of the cabbage seed weevil – significant correlations between abundance of C. obstrictus monitored in the field border and pod damage caused by D. brassicae inside the field were found. Insecticide treatment showed no effect as the amount of pod damage inside an insecticide-free control zone did not differ from the amount of pod damage outside the insecticide free control zone. Nonetheless, insecticides had been used by the farmers, indicating the need for development of more refined and more rapidly available monitoring and decision tools for farmers to improve IPM strategies for pest control of C. obstrictus and D. brassicae and to reduce insecticide use.